Legal review of dumping practices in Indonesia: A comparative study of international economic law and Sharia economic law - Wafa Ibra Syahra; Chairul Fahmi; Shabarullah Shabarullah (Priviet Social Sciences Journal, 2026)
Dumping is an international trade practice that can distort markets and harm domestic industries in importing countries, prompting the development of anti-dumping policies as trade protection instruments. This study aims to analyze the regulation and implementation of anti-dumping policy in Indonesia, examine its conformity with international trade law principles under the World Trade Organization (WTO) framework, and assess dumping and anti-dumping practices from the perspective of Sharia economic law. This study employs a normative juridical method using statutory, conceptual, and comparative law approaches, drawing on secondary data such as international agreements (GATT 1994 and the WTO Anti-Dumping Agreement), national legislation (Law No. 7 of 2014 and Government Regulation No. 34 of 2011), and scholarly literature on international and Islamic economic laws. The findings indicate that, normatively, Indonesia’s anti-dumping regulations have adopted WTO principles, particularly regarding the determination of dumping margins, material injury, and causation. However, in practice, the implementation of anti-dumping measures through the Indonesian Anti-Dumping Committee (KADI) continues to face procedural constraints and challenges in effectively protecting domestic industries. From the perspective of Sharia economic law, dumping is viewed as being inconsistent with the principles of justice, the prohibition of harm, and the ethical norms of fair competition. Therefore, Indonesia’s anti-dumping policy should be strengthened not only to ensure compliance with WTO law but also through the internalization of substantive justice values, as emphasized in Sharia economic law.